2005
DOI: 10.1007/s00125-005-1849-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of S21403 (mitiglinide) on postprandial generation of oxidative stress and inflammation in type 2 diabetic patients

Abstract: Aim/hypothesis: Evidence suggests that postprandial hyperglycaemia may be a cardiovascular risk factor in diabetes. Oxidative stress and inflammation are involved in the pathogenesis of diabetic complications and previous studies have shown increased oxidative stress and inflammation in the postprandial phase in diabetic patients. The aim of the present study was to evaluate whether controlling postprandial hyperglycaemia with S21403 (mitiglinide) is accompanied by a reduced generation of oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…It has been reported that intermittent hyperglycemia (glucose spikes) induces apoptosis of vascular endothelial cells when compared with persistent hyperglycemia [13] and that mitiglinide inhibits markers of oxidative stress and inflammation caused by postprandial hyperglycemia [14]. Continuous improvement in postprandial hyperglycemia over the long term as confirmed in this study is considered highly significant clinically.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that intermittent hyperglycemia (glucose spikes) induces apoptosis of vascular endothelial cells when compared with persistent hyperglycemia [13] and that mitiglinide inhibits markers of oxidative stress and inflammation caused by postprandial hyperglycemia [14]. Continuous improvement in postprandial hyperglycemia over the long term as confirmed in this study is considered highly significant clinically.…”
Section: Discussionsupporting
confidence: 63%
“…This rise was dependent upon oxidative mechanisms, as concomitant infusion of glutathione as a reducing agent abolished the effect [11]. In further support of these data, agents that increase insulin secretion and decrease postprandial glycaemia, such as mitiglinide, blunt the increase both in oxidative stress and inflammatory markers [12]. Similar results were obtained upon a glucose challenge in vivo or in vitro, which up-regulated inflammatory genes [intercellular adhesion molecule (ICAM)-1, TNF-a, IL-6], especially in subjects with the metabolic syndrome [13].…”
Section: Fasting/feeding Statementioning
confidence: 58%
“…The unfavourable postprandial effects on inflammation and endothelial cell function can be attenuated by hypoglycaemic agents, e.g. mitiglinide [20], glibenclamide [18], acarbose [21] or by the antioxidant glutathione [13,14]. In these studies, the hypoglycaemic agent was compared with placebo, and different treatment regimens have not been compared.…”
mentioning
confidence: 99%